Réponses

  • Utilisateur Brainly
2014-03-09T15:20:57+01:00
Bonjour,

AB = 2x+1 pour x =3, = 6+1 = 7
AF = x+3, pour x = 3, = 6

2) A FECD = (2x+1)[(2x+1)-(x+3)]
                 = 2x+1)(x-2)
                 = 2x²-4x+x-2
                 = 2x²-3x-2
pour x = 3 = 18-9-2 = 7

partie B :
1) FD = (2x+1)-(x+3)
         = x-2

2) A AFCD = FD*DC
                 = (2x+1)(x-2)
                 = 2x²-4x+x-2
                 = 2x²-3x+2

3) A ABCD = (2x+1)²
                 = 4x²+4x+1
     A ABEF = (2x+1)(x+3)
                   = 2x²+6x+x+3
                   = 2x²+7x+3

4)A ABCD- A ABEF =
  (2x-1)²-(2x+1)(x+3) =
   (4x²-4x+1)-(2x²+7x-3) =
   4x²-4x+1-2x²-7x+3 =
   2x²-11x+4

5) facto